Brain Gray Matter Alterations in Hepatic Encephalopathy: A Voxel-Based Meta-Analysis of Whole-Brain Studies - Zhu, Licheng; Zhang, Weihua; Chen, Lei; Ren, Yanqiao; Cao, Yanyan; Sun, Tao; Sun, Bo; Liu, Jia; Wang, Jing; Zheng, Chuansheng (Frontiers in Human Neuroscience, 2022)
Background: Previous studies on voxel-based morphometry have found that there were gray matter alterations in patients with hepatic encephalopathy. However, the reported results were inconsistent and lack a quantitative review. Therefore, this study aims to a quantitative meta-analysis of voxel-based morphometry analysis on hepatic encephalopathy patients. Methods: The studies in our meta-analysis were collected from Pubmed, Web of Science and Embase, which were published from January 1947 to October 2021. The seed-based d mapping method was applied to quantitatively estimate the regional gray matter abnormalities in HE patients. Meta-regression was applied to evaluate the relationship between plasma ammonia and gray matter alteration. Results: There were nine studies, with sixteen datasets consisting of 333 participants with HE as well as 429 healthy controls. The pooled and subgroup meta-analyses showed gray matter increased in bilateral thalamus and calcarine fissure, but decreased in bilateral insula, basal ganglia, anterior cingulate gyrus and cerebellum. The meta-regression showed that the plasma ammonia was positively associated with gray matter in the left thalamus while negatively associated with gray matter in the cerebellum and bilateral striatum. Conclusion: Gray matter volume in hepatic encephalopathy patients largely varied and could be affected by plasma ammonia. The findings of this study could help us to better understand the pathophysiology of cognitive dysfunction in hepatic encephalopathy patients.